Live-Cell Mesothelioma Biobank to Explore Mechanisms of Tumor Progression - Oehl, Kathrin; Kresoja-Rakic, Jelena; Opitz, Isabelle; Vrugt, Bart; Weder, Walter; Stahel, Rolf; Wild, Peter; Felley-Bosco, Emanuela (Frontiers in Oncology, 2018)
Experimental models closely representing in vivo conditions allow investigating mechanisms of resistance. Our aims were to establish a live-cell biobank of malignant pleural mesothelioma (MPM) samples, and to obtain proof of principle that primary culture chemoresistant models, mimicking tumor progression observed in patients, can be obtained in vitro, providing a useful tool to investigate underlying mechanisms. Primary mesothelioma cultures were established from 235 samples between 2007 and 2014. Of two MPM patients, primary cultures obtained at different time points: at initial diagnosis, after neoadjuvant treatment at surgery and/or after tumor recurrence, were deeply investigated. Cells and corresponding tumor tissue were characterized by mesothelial protein and gene expression analysis. In addition, primary cultures from chemo naïve patients were exposed to increasing doses of cisplatin/pemetrexed during three months and compared with non-treated cells in a cytotoxicity assay, and by selected profiling of senescence markers. In vitro chemoresistance in the primary mesothelioma cell cultures was associated with increased Thy1 (CD90) expression. Thy1 expression in MPM samples was significantly associated with poor overall survival in the TCGA MPM cohort. Our results illustrate that the establishment of a large live-cell MPM biobank contributes to a better understanding of therapy resistance observed in vivo, which eventually may lead to a more logical approach for developing new treatment strategies.